Management of finger joint dislocation and fracture-dislocations in athletes - Miller, E. A.; Friedrich, J. B. (Clinics in Sports Medicine, 2020)
Although finger joint dislocations are generally thought of as benign by many athletes and assumed to be a sprain, these injuries represent a spectrum that includes disabling fracture-dislocations. Failure to recognize certain dislocations or fracture-dislocations may result in permanent deformity and loss of motion. Simple dislocations are frequently amenable to early return to play with protection; however, more complex injuries may require specialized splinting or surgery. Delay in diagnosis of unstable proximal interphalangeal fracture-dislocations may require reconstruction or fusion. Early diagnosis and appropriate treatment are essential to ensure optimal functional results.